Twenty-Year Evolution of Hepatitis B Virus and Human Immunodeficiency Virus Prevalence and Incidence in Voluntary Blood Donors in Côte d'Ivoire. (16th March 2018) - Seri, Benjamin; Minga, Albert; Gabillard, Delphine; Dembele, Bamori; Konate, Seidou; Le Carrou, Jérôme; Dohoun, Lambert; Abo, Yao; Karcher, Sophie; Coffie, Patrick; N'Dri-Yoman, Thérèse; Attia, Alain; et al.
Abstract: Background: Hepatitis B virus (HBV) and human immunodeficiency virus (HIV) share common risk factors. The parallel description of their frequency over time may help capture their similarities and differences. Methods: Using data from the National Transfusion Center of Abidjan, we estimated the following over a 20-year period: (1) the prevalence of HIV and hepatitis B surface antigen (HBsAg) positivity at first contact; and (2) the incidence of HIV and HBsAg seroconversion in negative first-time blood donors. Results: Between 1992 and 2012, 422319 donors (men [M] = 74%) provided 1063825 blood donations. For first-time donors, HIV prevalence decreased from 7.1% (M = 5.9%, women [W] =11.0%) in 1992–1994 to 1.1% (M = 0.8%, W = 2.0%) in 2010–2012. Prevalence of HBsAg positivity remained stable at 10.8% (M = 11.7%, W = 7.3%) in 1992–1994 to 11.1% (M = 12.5%, W = 7.1%) in 2010–2012. Among regular donors (N = 129256), the incidence of becoming HIV or HBsAg positive, respectively, decreased from 4.9 per 100 (M = 4.5, W = 8.6) and 7.3 per 100 person-years (M = 7.8, W = 2.3) in 1992–1994 to 0.07 (M = 0.06, W = 0.11) and 0.2 per 100 person-years (M = 0.2, W = 0.2) in 2010–2012. Conclusions: Human immunodeficiency virus prevalence and incidence decreased dramatically over time, whereas HBV prevalence remained stable. Incidence of HBsAg seroconversion, although decreasing, still reached unexpected levels, suggesting that the risk of HBV infection in adults may be higher than expected. Hepatitis B surface antigen-negative blood-donors should be offered HBV vaccination.